1985
DOI: 10.1002/bjs.1800721225
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a somatostatin analogue SMS 201-995 on hepatic haemodynamics in the pig and on intravariceal pressure in man

Abstract: The effects of a somatostatin analogue, SMS 201-995, on hepatic haemodynamics in the pig and on intravariceal pressure in man were studied. An infusion of 250 micrograms/h SMS 201-995 significantly reduced portal pressure, portal venous flow and hepatic artery flow in the pig. These changes in hepatic haemodynamics were accompanied by a reduction in cardiac output, a reflex slowing of the heart and an increase in arterial blood pressure. Splanchnic vascular resistance was increased following SMS 201-995 admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
2

Year Published

1992
1992
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(27 citation statements)
references
References 10 publications
1
24
0
2
Order By: Relevance
“…As a result octreotide was shown to lower azygos blood flow [3]and variceal pressure [4]. Therefore, octreotide has been evaluated for both the adjuvant medical treatment of acute variceal bleeding [5, 6, 7]and the prophylaxis of rebleeding [8].…”
Section: Introductionmentioning
confidence: 99%
“…As a result octreotide was shown to lower azygos blood flow [3]and variceal pressure [4]. Therefore, octreotide has been evaluated for both the adjuvant medical treatment of acute variceal bleeding [5, 6, 7]and the prophylaxis of rebleeding [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, the results of those studies, which were mainly based on hemodynamic measurements and especially on calculation of the portosystemic shunt degree, have been criticized as being possibly affected by a number of imponderable and in many cases unknown factors [20][21][22] . It is therefore understood why similar studies from various research centers often resulted in completely different conclusions [23][24][25][26][27] . This study was designed in order to avoid similar problems by directly investigating lower esophageal pathology as shown in a previous study conducted in our department, where early octreotide administration seemed to attenuate the development of esophageal varices in cirrhotic rats [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Bolus injection appears to have important hemodynamic effects as compared to constant infusion (table 5), and may be the preferred method of administration [57]. Octreotide also can significantly reduce portal pressure [58,59], collateral blood flow [60], and AzBF [61] in cirrhotics -surrogate markers of variceal blood flow, but, like for natural somatostatin, there are some studies reporting no hemodynamic effect. A recent study [62] actually showed that intravenous bolus injection of octreotide does increase intraesophageal variceal pressure (IEVP), thus suggesting that this mode of administration is not appropriate as a first-line therapy for variceal hemorrhage.…”
Section: Somatostatin For Upper Gi Bleedingmentioning
confidence: 99%